Nanomeshes of highly crystalline nitrogen-doped carbon encapsulated Fe/Fe3C electrodes as ultrafast and stable anodes for Li-ion batteries1. Issue 29 (7th August 2015) - Zhou, Jinqiu; Qian, Tao; Yang, Tingzhou; Wang, Mengfan; Guo, Jun; Yan, Chenglin
<x xml:space="preserve">Abstract</x> Nanomeshes of highly crystalline nitrogen-doped carbon encapsulated Fe/Fe3C electrodes as ultrafast and stable anodes for Li-ion batteries have been demonstrated.